Structure-property relationships: "Double-tail versus double-flap" ruthenium complex structures for high efficiency dye-sensitized solar cells. (1st January 2019) - Su, Rui; Ashraf, Saba; El-Shafei, Ahmed
Graphical abstract: Highlights: Ru(II) sensitizers, FS01-FS06, were synthesized with julolidine-derived ligands. Sensitizers were classified by their different substructures ("flaps" and "tails"). The highest J SC was observed for device employing the sensitizerFS05 . FS05 (8.16%) outperformed the benchmarkN719 (7.75%) in the photovoltaic performance. The double-tail versus double-flap effect on the photovoltaic properties were discussed. Abstract: Six novel heteroleptic amphiphilic polypyridyl Ruthenium (II) complexes, codedFS01 -FS06, with hetero-aromatic electron-donor ancillary ligands containing julolidine-derived moieties were synthesized to investigate the relationship between structure modulations of electron donors of Ru(II) dyes and their photophysical, electrochemical and photovoltaic properties for dye-sensitized solar cells (DSSCs). These modulations include: Ru(II) complexes with double "tails" (i.e. tetramethyl groups attached to the end of julolidine-based antennas, FS04 ) compared to the ones without double "tails" (FS01 ); complexes with double small "flaps" (i.e. small acyclic electron donor auxochromes ortho to the CH = CH bridge of stilbazole, FS02, FS05 ) compared to the ones with double large "flaps" (FS03, FS06 ). Their low energy metal-to-ligand charge transfers (MLCT) band and molar absorptivities were all better than those of the benchmark, N719 . It was also shown that the incorporation of double "flaps" into the ancillary ligands caused a slight red shift of light absorption. The photovoltaic properties were evaluated under 1.5 AM standard illumination condition and compared toN719 . The highest photocurrent density ( JSC ) was observed for the complex with double "tails" and double small "flaps" (FS05 ). The overall conversion efficiency for devices employing julolidine-derived Ru (II) complexes was in the following orderFS05  > FS02  > FS04  > FS01  > FS06  > FS03 .FS05 (8.16%) outperformed the benchmarkN719 (7.75%) in the photovoltaic performance, which is due to its best light-harvesting ability, highest molar extinction coefficient and smallest energy band gap among all the six dyes. To probe the interrelationship among julolidine-based electron donors of ancillary ligands, photocurrent and photovoltage of these dyes, the equilibrium molecular geometries of the ancillary ligands were calculated using DFT. The equilibrium molecular geometries of these dyes the photocurrent and photovoltage are dependent on the donating effect of alkyloxy auxochromes, the steric effect generated from the auxochromes and julolidine moieties, and the orientation of longer alkyloxy group. The introduction of double "tails" resulted in less dye aggregation and higher charge recombination resistance, leading to higher photocurrents and photovoltages in the solar cell performances. Despite of the donating effect of alkyloxy groups, the bulky double "flaps" mainly jammed the hole transportation between the redox couple of the electrolyte and the HOMO of thiocyanate groups (−NCS), translating into the decrease of photocurrent.